2012
DOI: 10.1016/j.eja.2011.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of parameters of the ‘Virtual Fruit’ model to design peach genotype for sustainable production systems

Abstract: Designing sustainable production systems that are respectful of the environment and produce safe food of quality is a challenge for the future. A critical step is to find the best combinations of genetic resources and cultural practices adapted to target environments. The objective of this work is to illustrate how an ecophysiological process-based simulation model could be possibly used to design genotypes and to propose innovative production systems, by applying a methodology of optimization. As example, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 52 publications
0
27
0
1
Order By: Relevance
“…photosynthesis) or agronomic (e.g. production) traits simultaneously in a multi-objective approach as recently performed by Quilot-Turion et al (2012). In the next future, the use of in silico scenarios and optimization procedures should allow researchers, growers and breeders to better account for antagonistic effects of input parameters, possibly at several scales of tree organization, and their combined effects on multiple objectives.…”
Section: Perspectives: Integrating Architectural Traits In Breeding Pmentioning
confidence: 99%
“…photosynthesis) or agronomic (e.g. production) traits simultaneously in a multi-objective approach as recently performed by Quilot-Turion et al (2012). In the next future, the use of in silico scenarios and optimization procedures should allow researchers, growers and breeders to better account for antagonistic effects of input parameters, possibly at several scales of tree organization, and their combined effects on multiple objectives.…”
Section: Perspectives: Integrating Architectural Traits In Breeding Pmentioning
confidence: 99%
“…Many papers have been published on the use of evolutionary algorithms for ideotype model-based design. For the sake of conciseness, we mention only the works of Letort et al (2008) on beech trees, of Qi et al (2010) on maize, of Lu et al (2012) on wheat, of Quilot-Turion et al (2012) and Sidi et al (2014) on peach, and of Ding et al (2016) on rice.…”
Section: Introductionmentioning
confidence: 99%
“…In a case-study on optimizing maturity and density for a sunflower crop, they proved the potential power of the concept. Recent works making the connection of advanced optimization algorithms with process-based models confirmed that the approach is valuable to identify trade-off in complex systems (Qi et al, 2010; Quilot-Turion et al, 2012) and that specific adaptation of genotypes to local environmental conditions confers an advantage over broad adaptation (Hammer et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Nature-inspired optimization algorithms (e.g., genetic algorithms and particle swarm optimization algorithms) are increasingly used (deVoil et al, 2006; Letort et al, 2008; Qi et al, 2010; Ould-Sidi and Lescourret, 2011; Grechi et al, 2012; Kadrani et al, 2012; Quilot-Turion et al, 2012; Memmah et al, 2015). These algorithms both do not require any derivative information and enable exploring highly dimensional solution spaces.…”
Section: Introductionmentioning
confidence: 99%